La implementación del derecho de la competencia y la ley orgánica de regulación y control del poder de mercado en el Ecuador - Vivanco Maldonado, Edgar Leonardo (2014)
The competition law, which Americans call antitrust law (in English Antitrust Law), can be described as the set of legal rules intended to regulate the business potential of a given market, in the public interest or present power. In practice, the competition law prohibits engaging in restrictive practices of competition, acquiring a dominant position in the market through the implementation of such practices and abuse of dominant position. The competition law represents positivization of economic concepts. The purpose of the application is marked by the prevailing economic system in the state that adopts it. However, unlike many legal institutions that have changed little over the centuries, the competition law in a span of just over a hundred years of existence has evolved significantly. The movement of the economic analysis of law, known in English law and economics, has led to novel insights about human behavior and the organization of society through law. Indeed, in the case of competition law economics determine the evolution of policies, laws and decisions of the authorities responsible for applying them. The Antitrust law had its origins in the USA, in 1890, because they began to observe certain practices that alter the proper development of the industry. Rapidly in most countries of the world decided to adopt legislation regulating infringements on the market. In the case of Ecuador, was not, as recently as 2011 the National Assembly passed the so-called Organic Law for the Regulation and Control of Market Power, rule of law responsible for supervising the activities of traders in the Ecuadorian market. As is then that, in the development of this thesis I will take care of analyzing the competition law, its origins, it´s evolution over time, as well as the implementation of this branch of law in Ecuador through the enactment of Organic Law for the Regulation and Control of Market Power.